THE EFFECT OF TIME DURATION IN THE NETWORK AND RADIAL METHOD TOWARD THE ACCURACY IN MEASURING THE DEFORMATION AT MURIA - Ari Nugroho; Hadi Suntoko (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2011)
ABSTRACTTHE EFFECT OF TIME DURATION IN THE NETWORK AND RADIAL METHOD TOWARD THE ACCURACY IN MEASURING THE DEFORMATION AT MURIA. The Deformation monitoring activities in the vicinity of Mount Muria are recommended by the IAEA (International Atomic Energy Agency) to be done for 5 years. The purpose of these activities is to determine the rate of the deformation caused by the volcanic activity of Mount Muria, as a basic study in analyzing the volcanic hazard toward the NPP (Nuclear Power Plant). The whole coordinate points measured encompass the district of Jepara, Pati, Demak, and Kudus. In 2010 deformation measurements were periodically conducted for 4 times a year using two geodetic GPS units of Trimble R7 GNSS type through the network method. The measurements were carried out at seven points of interest and at one reference point in March, April, May and December. Each session of the measurements was performed for 2.5 hours. In 2011 the deformation measurements were periodically conducted for 4 times a year by means of the radial method. The measurements were made at eight points of interest and at one reference point in April and May, June and July. Each session of measurements was performed for 10 hours. Based on the results of the measurements by means of the network method in 2010, it was concluded that the range of horizontal and vertical accuracy is between 6-10 mm and 25-46 mm., while the results of the measurements of the radial method in 2011 is 4-7 mm, and 16-28 mm respectively. Furthermore, it provides the evidence that the radial method tends to has better result than the network method if it is applied 4 times longer than the network method, resulting the accuracy below 7 mm and 28 mm for horizontal and vertical respectively.Keyword: deformation, global positioning system, differential method ABSTRAKPENGARUH WAKTU PENGUKURAN PADA METODE JARING DAN RADIAL TERHADAP AKURASI DATA DEFORMASI DI MURIA. Kegiatan monitoring deformasi di sekitar Gunung Muria, Jawa Tengah direkomendasikan oleh IAEA (International Atomic Energy Agency) untuk dilakukan paling kurang selama 5 tahun. Tujuan kegiatan ini untuk mengetahui besarnya nilai deformasi yang disebabkan oleh aktivitas vulkanik Gunung Muria, sebagai dasar untuk analisis bahaya Gunung Muria terhadap tapak PLTN (Pembangkit Listrik Tenaga Nuklir). Titik koordinat yang diukur meliputi Kabupaten Jepara, Pati, Demak dan Kudus. Pada tahun 2010 telah dilakukan pengukuran deformasi secara periodik selama 4 kali dalam setahun menggunakan 2 unit GPS geodetik jenis Trimble R7 GNSS dengan metode jaring. Pengukuran dilakukan di 7 titik pengamatan dan satu titik referensi di Bulan Maret, April, Mei dan Desember. Setiap sesi dari pengukuran dilakukan selama 2,5 jam. Pada tahun 2011 telah dilakukan pengukuran deformasi secara periodik selama 4 kali dalam setahun dengan metode radial. Pengukuran dilakukan di 8 titik pengamatan dan 1 titik referensi di Bulan April dan Mei, Juni, serta Juli. Setiap sesi dari pengukuran dilakukan selama 10 jam. Berdasarkan hasil pengukuran dengan metode jaring pada tahun 2010 diperoleh kesimpulan bahwa keakurasian horizontalnya berkisar dalam rentang 6 – 10 mm dan keakurasian vertikalnya adalah 25 – 46 mm. Sedangkan hasil pengukuran dengan metode radial pada tahun 2011 diperoleh kesimpulan bahwa keakurasian pengukuran horisontalnya berkisar dalam rentang 4 – 7 mm, dan keakurasian vertikalnya adalah 16 – 28 mm. Hal ini membuktikan bahwa jika dilakukan 4 kali lebih lama dari metode jaringan, maka metode radial cenderung memberikan akurasi yang lebih baik yaitu di bawah 7 mm untuk akurasi horizontal dan dibawah 28 mm untuk akurasi vertikal.Kata kunci: deformasi, global positioning system, metode diferensial